Optically pumped AlGaN quantum‐well lasers at sub‐250 nm grown by MOCVD on AlN substrates. Issue 2 (20th January 2014) - Liu, Yuh‐Shiuan; Lochner, Zachary; Kao, Tsung‐Ting; Satter, Md. Mahbub; Li, Xiao‐Hang; Ryou, Jae‐Hyun; Shen, Shyh‐Chiang; Yoder, P. Douglas; Detchprohm, Theeradetch; Dupuis, Russell D.; Wei, Yong; Xie, Hongen; et al.
Abstract In this study, we employed bulk (0001) AlN substrates for the metalorganic chemical vapor deposition growth of AlGaN multi‐quantum‐well heterostructures in an Aixtron 6 × 2″ close‐coupled showerhead reactor. The wafers were fabricated into cleaved bars with a cavity length of ∼1 mm. Two different layer structure designs are presented in this work. Both laser bars were optically pumped by a pulsed 193 nm ArF excimer laser at room temperature. The lasing wavelengths are 243.5 nm and 245.3 nm with threshold power density 427 kW/cm2 and 297 kW/cm2, respectively. Both laser bars showed transverse electric‐polarization‐dominated optical emission when operating above threshold. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)